Structural and functional characterization of the cytotoxic protein ledodin, an atypical ribosome-inactivating protein from shiitake mushroom (Lentinula edodes) - Citores, Lucía (2023)
We have purified ledodin, a cytotoxic 22-kDa protein from shiitake mushroom (Lentinula edodes) consisting of a 197 amino acid chain. Ledodin possessed N-glycosylase activity on the sarcin-ricin loop of mammalian 28S rRNA and inhibited protein synthesis. However, it was not active against insect, fungal, and bacterial ribosomes. In vitro and in silico studies suggested that ledodin exhibits a catalytic mechanism like that of DNA glycosylases and plant ribosome-inactivating proteins. Moreover, the sequence and structure of ledodin was not related to any protein of known function, although ledodin-homologous sequences were found in the genome of several species of fungi, some edible, belonging to different orders of the class Agaricomycetes. Therefore, ledodin could be the first of a new family of enzymes widely distributed among this class of basidiomycetes. The interest of these proteins lies both, in the fact that they can be a toxic agent of some edible mushrooms and in their application in medicine and biotechnology.